MEANING OF PHRASEOLOGICAL UNITS IN ARABIC AND UZBEK LANGUAGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article contains information on the meanings of phraseological units used in Arabic and Uzbek languages and their mutual relationships. At the same time, it is explained with the help of several examples of phraseologies of the two languages, which have formed a common meaning.